PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE UNTUK MENINGKATKAN KETERAMPILAN MENULIS RINGKASAN SISWA KELAS V SEKOLAH DASAR - Erlina Wibowo, - (2023)
This research departs from the problem of low writing skills of fifth grade elementary school students. Based on observations at a school in Bogor Regency, students experienced some difficulties and were not interested in writing. From the results of learning to write summaries for class V students at SDN Cikahuripan 01, there were about 24 of the 28 students in class V who had not yet reached the minimum completeness criteria. This study aims to describe the application of the round table cooperative learning model to improve the summary writing skills of fifth grade elementary school students. The research method that will be used is the classroom action research method which is carried out in two cycles. The research design used is the spiral model from Kemmis & Mc. Taggart which consists of planning, action, observation, and reflection. The subjects in this study were the fifth grade elementary school students, totaling 28 people. Data collection techniques used are observation, interviews and tests. The results showed that the cooperative learning model of the round table type could improve the summary writing skills of fifth grade elementary school students. In the results of the summary writing test analysis in the first cycle, students got an average score of 67.5 with a completeness percentage of 25% and experienced an increase in the second cycle, students got an average score of 85 with a completeness percentage of 100% with the "very good" criteria.